ANALISIS PERBEDAAN PENDAPATAN PETANI CABAI KEMITRAAN INDOFOOD DENGAN PETANI GUREM DI KECAMATAN BALIK BUKIT, KABUPATEN LAMPUNG BARAT - Buchori Buchori; Eko Yudi Prasetiyo; Tri Mardiono (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The purpose of this research is to study whether there is a difference in the income of Indofood Chili Farmers and Gurem Farmers in Balik Bukit District, West Lampung Regency